SOME REMARKS ON PERSIAN VARIATIONS IN THE UZBEK LANGUAGE VOCABULARY (American Journal of Pedagogical and Educational Research, 2023)
This article provides detailed information on the use of the affix -ak , meaning smallness, inferiority, deficiency of the vocabulary of the Uzbek language.